Aktivitas Ekstrak Daun Suji (Dracaena angustifolia Roxb.) sebagai Antianafilaksis Kutan Aktif pada Mencit Putih Jantan - Yufri Aldi; Muhammad Syafrudin; Elisma Elisma (Jurnal Sains Farmasi & Klinis, 2015)
An assay of the active cutaneous anti anaphylactic of the ethanolic extract of the Dracaena angustifolia Roxb. On male white mice has been studied. The assay was done by giving three different doses (100,300, 900 mg per/kg bw). Allergic reaction was induced by giving egg’s albumin as antigen. The anti anaphylactic effect was determined by measurement of the pro long of occurrence time, the dereased in diameter and the color intensity of the blue bump formed by using blue evan’s solution as indicator which was given intravenously. Result indicated the ethanolic extract of Dracaena angustifolia Roxb. (100, 300, 900 mg/kg bw) had significant effect for each dose (p<0.01). The dose of 900 mg per kg body weight showed best effect.